Effectiveness Comparison of Mothers' In-person Versus Written Nutritional Education Intervention on Infant Growth in Iran - Nemati Ali, PhD; Tazakori Zahra, PhD; Maryam Namadi Vosogh, MSN; Nazila Vosoghi, MSN; Maryam Zare, PhD; Afroz Mardi, PhD; Adham Davoud, PhD; Hamidzadeh Arbabi Yousef, PhD (Global Health and Education Projects, Inc., 2015)
Background: In 1990, the Iranian Ministry of Health implemented a health plan to increase mothers' knowledge of infant feeding using health workers and health volunteers. This study evaluates the effects of nutrition education on mothers' knowledge and whether increase in mothers' knowledge was associated with increase in growth of their children in Ardabil, Iran. Methods: A quasi-experimental study of the impact of written nutritional education and in-person nutritional education given to the participants (mothers) from urban health centers by health workers and health volunteers. Sixteen urban health centers located in Ardabil, Iran, were selected randomly for nutritional education. A group of 303 mothers with infants younger than 6 months of age from 16 health centers participated in this study. Height-for-age Z scores and weight-for age Z scores were calculated based on the National Center for Health Statistics reference values. Results: There were significant differences between maternal nutritional knowledge before and after the intervention in all groups. However, the in-person method of instruction given by health workers was more effective in increasing mothers' knowledge than those in non-health worker volunteers intervention group. There were also significant differences between the growth rates of infants' heights and weights before and after the intervention. Conclusions and Global Health Implications: In line with the aims of the government's plan, the education given by health volunteers from non-governmental organizations was effective. However, it was less effective than the one given by professional health workers.